Lp-PLA2, a potential protector of lung cancer patients complicated with pleural effusion from lung diseases, proves effective for the diagnosis and pathological classification of lung cancer - Jing Wang; Minya Jin; Yijun Chen; Yuan Yuan; Yi Ruan; Guoguang Lu (Translational Oncology, 2021)
Abnormal lipid metabolism plays a crucial role in cancers, but few studies have investigated the relationship between lipoprotein-associated phospholipase A2 (Lp-PLA2) and lung cancer. In this study, 58 benign lung disease (LB) and 57 lung cancer (LC) patients complicated with pleural effusion (PE) were included, and their fasting serum and PE samples were collected. Results showed that serum Lp-PLA2 in the LC group was lower than that in the LB group, and other serum lipids were higher (P < 0.05). Tumor markers from serum and the PE samples of LC patients were higher than those in the LB group (P < 0.05). Serum prealbumin (PA) in LC patients was higher than that in the LB group, and serum C-reactive protein (CRP) and procalcitonin (PCT) were lower (P < 0.05). In the LC group, serum Lp-PLA2 concentration was positively correlated with serum triglyceride (TG), Lp (a), carbohydrate antigen 199 (CA199), nutritional markers, and Lp-PLA2 in PE and negatively correlated with serum high-density lipoprotein cholesterol (HDLC), Apolipoprotein A1 (APOA1), CRP, PCT, and alpha fetoprotein (AFP) and LDH in PE. The ROC curve showed that the cutoff level of serum Lp-PLA2 for diagnosing LC was 226.685 (U/L) (sensitivity: 0.632, specificity: 0.793), while the C-index of the nomogram model combined with serum Lp-PLA2, age, and gender was 0.750. In LC patients, the higher serum Lp-PLA2 indicated higher probability of adenocarcinoma and lower probability of squamous cell carcinoma (SCC). In conclusion, Lp-PLA2 may be a protective factor of lung cancer among lung disease patients complicated with pleural effusion, and it would facilitate the diagnosis and pathological classification of lung cancer.